UPAYA MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS VII B SMPN 14 DENPASAR MELALUI PENERAPAN MODEL PEMBELAJARAN PBL - Anestasya Sirait; Putu Ledyari Noviyanti (Universitas Islam Sumatera Utara, 2025)
Low learning motivation is one of the main obstacles in mathematics education, particularly due to the abstract nature of the subject, which often causes students to become passive and less enthusiastic. This study aims to improve students’ motivation in learning mathematics through the implementation of the Problem-Based Learning (PBL) model among seventh-grade students at SMP Negeri 14 Denpasar. The research employed a classroom action research (CAR) approach, conducted over two learning cycles. The study involved 41 students as participants. Data were collected through observations and learning motivation questionnaires. The results showed an increase in students’ learning motivation from an initial 38% to 70% in the first cycle and 91% in the second cycle. This improvement indicates that the application of the PBL model significantly enhances students’ active participation and enthusiasm in learning mathematics. Therefore, PBL can be considered an effective instructional strategy to address low learning motivation in mathematics among junior high school students.